Alterations in Microrhizome induction, shoot multiplication and rooting of Ginger (Zingiber officinale Roscoe) var. Bentong with regards to sucrose and plant growth regulators application - Ahmad Zahid, Nisar; Jaafar, Hawa Z. E.; Hakiman, Mansor (Multidisciplinary Digital Publishing Institute, 2021)
Ginger (Zingiber officinale Roscoe) var. Bentong is a monocotyledon plant that belongs to the Zingiberaceae family. Bentong ginger is the most popular cultivar of ginger in Malaysia, which is conventionally propagated by its rhizome. As its rhizomes are the economic part of the plant, the allocation of a large amount of rhizomes as planting materials increases agricultural input cost. Simultaneously, the rhizomes’ availability as planting materials is restricted due to the high demand for fresh rhizomes in the market. Moreover, ginger propagation using its rhizome is accompanied by several types of soil-borne diseases. Plant tissue culture techniques have been applied to produce disease-free planting materials of ginger to overcome these problems. Hence, the in vitro-induced microrhizomes are considered as alternative disease-free planting materials for ginger cultivation. On the other hand, Bentong ginger has not been studied for its microrhizome induction. Therefore, this study was conducted to optimize sucrose and plant growth regulators (PGRs) for its microrhizome induction. Microrhizomes were successfully induced in Murashige and Skoog (MS) medium supplemented with a high sucrose concentration (>45 g L−1). In addition, zeatin at 5–10 µM was found more effective for microrhizome induction than 6-benzylaminopurine (BAP) at a similar concentration. The addition of 7.5 µM 1-naphthaleneacetic acid (NAA) further enhanced microrhizome formation and reduced sucrose’s required dose that needs to be supplied for efficient microrhizome formation. MS medium supplemented with 60 g L−1 sucrose, 10 µM zeatin and 7.5 µM NAA was the optimum combination for the microrhizome induction of Bentong ginger. The in vitro-induced microrhizomes sprouted indoors in moist sand and all the sprouted microrhizomes were successfully established in field conditions. In conclusion, in vitro microrhizomes can be used as disease-free planting materials for the commercial cultivation of Bentong ginger.